Intelligent networks: telecommunications solutions for the 1990s - Chorafas, Dimitris N. (CRC Press Boca RatonUS, 1990)
Looks at the telecommunications perspective of the 1990s and the problems involved in the transition. Focuses on the strategic aspects of intelligent networks as well as their dynamics and the mechanics.